Factors Affecting Online Communication Due to Social Networks on Loyalty of Tourism Services Customers (Case Study: District 22 of Tehran) - Rasha Makoundi; Hossein Safarzadeh; Hassan Esmailpour; Mansoureh Aligholi (تحقیقات کاربردی علوم جغرافیایی)
Today, the Internet and virtual networks have become a major part of many people's daily lives, and social networking sites attract millions of people from all over the world, so word of mouth has shifted to the digital world. The present study was written to identify the impact of factors affecting online referral communication in social networks on the loyalty of tourism service customers. The present study is applied in terms of purpose and descriptive-analytical in terms of method. The statistical population of the study consisted of virtual network users who had experience traveling to the area. The sample size was estimated 384 people using Cochran's formula. In this study, SPSS and Amos software were used to analyze the data. Findings of this study showed that message attractiveness, resolution, quantity and clarity of the message have a positive and significant effect on customer loyalty of tourism services. Also, the results of this study showed that among the studied factors, the message quantity factor with an impact factor of 0.67 has the most impact.